2018
DOI: 10.3892/etm.2018.7139
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of middle cerebral artery aneurysm with a (LVIS) device: Comparison of LVIS stent and non‑LVIS stent

Abstract: Middle cerebral artery (MCA) aneurysm is a serious medical condition mainly occurring in the proximal and bifurcation tracts. Evidence has indicated that endovascular treatment is an effective surgical method for patients with MCA aneurysm. In the present study, the efficacy of endovascular treatment with low-profile visualized intraluminal support (LVIS) stent for MCA aneurysms was evaluated in comparison with that using a non-LVIS stent device. A total of 92 patients who underwent endovascular treatment of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our propensity score-matched cohort study showed that for wide-necked acutely RIAs, LVIS SAC yielded lower rates of perioperative overall procedure-related complications and intraprocedural aneurysm rupture than laser-cut SAC (5.6% vs 14.0%, P = 0.028; 0.7% vs 6.5%, P = 0.016). These results were similar to Chen’s study, which analyzed 92 cases of SAC for unruptured middle cerebral artery aneurysms and found that LVIS SAC significantly reduced the incidence of intraoperative aneurysm rupture compared with laser-cut SAC [ 38 ]. In addition, our present results indicated that the LVIS stent group had a higher complete occlusion rate and lower recurrence rate than the laser-cut stent group (92.7% vs 80.6%; 3.7% vs 9.7%).…”
Section: Discussionsupporting
confidence: 87%
“…Our propensity score-matched cohort study showed that for wide-necked acutely RIAs, LVIS SAC yielded lower rates of perioperative overall procedure-related complications and intraprocedural aneurysm rupture than laser-cut SAC (5.6% vs 14.0%, P = 0.028; 0.7% vs 6.5%, P = 0.016). These results were similar to Chen’s study, which analyzed 92 cases of SAC for unruptured middle cerebral artery aneurysms and found that LVIS SAC significantly reduced the incidence of intraoperative aneurysm rupture compared with laser-cut SAC [ 38 ]. In addition, our present results indicated that the LVIS stent group had a higher complete occlusion rate and lower recurrence rate than the laser-cut stent group (92.7% vs 80.6%; 3.7% vs 9.7%).…”
Section: Discussionsupporting
confidence: 87%
“…The “barrel technique” (pushing the stent across the aneurysm to make the stent partially protrude into the aneurysm) provides better protection for the wide aneurysm neck and the involved side-branches, and also enabled a better vessel attachment of the stent. A study comparing LVIS stent-assisted coiling (53 cases) and non-LVIS stent-assisted coiling (49 cases) for the treatment of unruptured MCA aneurysms also showed that coiling with LVIS stents increased treatment safety ( 16 ). Secondly, a modified antiplatelet regimen could help.…”
Section: Discussionmentioning
confidence: 99%
“…MCA proximal and distal aneurysms are relatively rare, and most previous studies of proximal and distal aneurysms focus on the selection of treatment options for aneurysm rupture. Few studies exist on the relationship between MCA geometry and the formation of proximal and distal aneurysms [24][25][26][27]. To the best of our knowledge, the relation of both the α and β to the formation of proximal and distal MCA aneurysms has not yet been reported.…”
Section: Morphological Features Between Mca Proximal and Distal Aneurmentioning
confidence: 99%